Correction: Cost comparison of nine-month treatment regimens with 20-month standardized care for the treatment of rifampicin-resistant/multi-drug resistant tuberculosis in Nigeria. - Florence O Bada (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pone.0241065.].